Experimental study on translation motion characteristics of Moored Symmetrical Semi-submersible in regular waves / Khairuddin, N.M....[et al.] - N.M., Khairuddin; Koto, Jaswar; A.R., Ain; J., Azhari; A., Najmie (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
This paper proposes to carry out experiment procedures to investigate the translation motion characteristics of symmetrical semi-submersibles in long crest regular waves. The hydrodynamic response of floating structures in waves is required to be modelled correctly to ensure stability and safety. The symmetrical semi-submersible model was constructed based on a scale ratio of 1:81 in this experiment and was installed with horizontal mooring lines in a wave dynamic basin. This paper also discusses the model preparation procedures, including the mooring lines setup, instrument setup and experiment setup, before conducting the experiment. According to the experiment data, the symmetrical moored semi-submersible experienced wave frequency motion and slow varying motion due to drift force and mooring lines for sway motion; while the heave and surge motion only experienced wave frequency motion.